2022
DOI: 10.21043/ziswaf.v9i1.13330
|View full text |Cite
|
Sign up to set email alerts
|

Determinant of Behavioral Intention to Use Digital Zakat Payment: The Moderating Role of Knowledge of Zakat

Abstract: <em>The potential for zakat in Indonesia is increasing over time. However, the value of the increase in zakat receipts is not proportional to the potential of zakat. Research on zakat behavior using digital platforms is important considering the lack of realization of zakat collection compared to the existing potential. This study develops the UTAUT model by adding knowledge of zakat as a moderated variable. A quantitative approach is used in this research. The number of respondents in this study was 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 27 publications
4
13
0
2
Order By: Relevance
“…The results of existing research support or are supported by several previous studies which found that social influence has a significant influence on interest in doing something, both in using a service to donating activities including, Interest in giving alms and donating through fintech is influenced by subjective norms (A. S. Kharisma & Putri, 2020). This research is contrary to the results found by several studies including (Pangestu, 2021) where, social influences or subjective norms have no significant impact on Muslim women's decisions to donate by choosing to use services from Alfamart (Cahyani et al, 2022) found that social influence has a positive effect on behavior using digital zakat, (Li et al, 2018) found that social influence had a positive effect on users' intention to donate money on a charity fundraising platform, (Usman, 2020) found that subjective norms or social influences affect interest in paying zakat through fintech, (Oliveira et al, 2016) found that social influences influence consumer intentions to make digital-based payments, (Kurniawan et al, 2022) regarding social influences affecting the intention to use digital zakat in the city of Malang, As for (Kasri & Yuniar, 2021) found that social influence had no effect on the Indonesian people's interest in paying alms and infaq Meanwhile, the significant impact of social influence on the interest of the Jayapura Muslim community to donate proves that although each individual has the freedom to think, behave and decide to act and express opinions, the recommendations and beliefs of several people around him can be one of the determining factors in deciding to do something. activities, in this case in donating to philanthropic institutions, whether non-religious or religious and whether they are private or owned by the local government.…”
Section: Source : Data Processed (2022)mentioning
confidence: 60%
See 2 more Smart Citations
“…The results of existing research support or are supported by several previous studies which found that social influence has a significant influence on interest in doing something, both in using a service to donating activities including, Interest in giving alms and donating through fintech is influenced by subjective norms (A. S. Kharisma & Putri, 2020). This research is contrary to the results found by several studies including (Pangestu, 2021) where, social influences or subjective norms have no significant impact on Muslim women's decisions to donate by choosing to use services from Alfamart (Cahyani et al, 2022) found that social influence has a positive effect on behavior using digital zakat, (Li et al, 2018) found that social influence had a positive effect on users' intention to donate money on a charity fundraising platform, (Usman, 2020) found that subjective norms or social influences affect interest in paying zakat through fintech, (Oliveira et al, 2016) found that social influences influence consumer intentions to make digital-based payments, (Kurniawan et al, 2022) regarding social influences affecting the intention to use digital zakat in the city of Malang, As for (Kasri & Yuniar, 2021) found that social influence had no effect on the Indonesian people's interest in paying alms and infaq Meanwhile, the significant impact of social influence on the interest of the Jayapura Muslim community to donate proves that although each individual has the freedom to think, behave and decide to act and express opinions, the recommendations and beliefs of several people around him can be one of the determining factors in deciding to do something. activities, in this case in donating to philanthropic institutions, whether non-religious or religious and whether they are private or owned by the local government.…”
Section: Source : Data Processed (2022)mentioning
confidence: 60%
“…Several studies have shown that the effectiveness of distribution in donating that is felt by donors has a positive effect in this case with the use of technology, including those carried out by (Ninglasari & Muhammad, 2021) analyze the role of digitalization in the management of zakat during the Covid-19 pandemic, (Kusumawardani, 2020) examines the influence of the quality of public governance, accountability and effectiveness on the intention of members of the Yogyakarta Indonesian Chinese Islamic Association (PITI) in paying zakat, (Muhammad & Saad, 2016) regarding the quality, accountability and effectiveness of public governance on the intention to pay zakat, (Hudaefi & Beik, 2020) Learn about digital zakat campaign tools during the Covid-19 outbreak, (Cahyani et al, 2022), developing the UTAUT model by adding zakat knowledge as a moderating variable on interest in paying zakat using a digital platform, (Wang et al, 2019) found that perceived donor effectiveness has a positive effect on the intention to donate through crowdfunding, (Farooq et al, 2020) presents a blockchain-based charity management platform that aims to provide a safe, transparent and efficient system for donations, (Kashif et al, 2018) found that informants or zakat actors prefer to donate zakat directly, this is due to a lack of trust in zakat institutions, (Choi et al, 2019) examines the mediating effect of online donations on youth donation awareness, as well as the pathways of online donations to intention to donate again in the future, (Rahman & Idrus, 2022) analyze the factors that influence online zakat payments, (Maleki & Hosseini, 2020) analyze the factors that influence the intention to donate through mobile payment applications, (Wiharjo & Hendratmi, 2019) about interest in paying zakat, infaq and alms online in Kuala Lumpur, (Jamaludin et al, 2017) regarding the perception of the use of zakat, infaq and alms online in Indonesia, (Ichwan, 2020) regarding muzzaki's decision to pay zakat, infaq and alms through fintech gopay, (Amalia, 2018) regarding individual interest in using Paytren sharia fintech as a means of payment for donation transactions, (Niswah et al, 2019a) regarding the interest of the Muslim millennial community in donating using the fintech platform, (Usman, 2020) about the use of fintech in donating, (Oktavendi, 2021) regarding the adoption of online ZIS payments by Generation Z, (Arwanita, 2022) researching interest in paying ZIS through BSI Mobile, (Lathifah, 2020) which ...…”
Section: Rotated Component Matrixmentioning
confidence: 99%
See 1 more Smart Citation
“…Huda and Gofur (2012) show that knowledge has a significant influence on the intention to pay professional zakat. Mukhlis and Beik (2013) and Cahyani et al (2022) confirm that knowledge is a significant predictor of individuals in paying zakat. From previous studies, the following hypothesis is formulated:…”
Section: Zakat Knowledge and Zakat Compliancementioning
confidence: 67%
“…Penelitian sebelumnya menjelaskan bahwa pada actual system pembayaran digital di India, ditemukan hubungan yang signifikan antara niat perilaku dan perilaku penggunaan (Patil et al, 2020). Pada pembayaran digital, niat untuk menggunakan aplikasi pembayaran digital terbukti berpengaruh positif terhadap penggunaan pembayaran digital (Cahyani et al, 2022). Perilaku penggunaan teknologi keuangan dipengaruhi oleh niat berperilaku (Tohang et al, 2021).…”
Section: Behavior Intention Terhadap Use Behaviourunclassified